Novejši prispevki k polemiki o avtentičnosti Slova o polku Igoreve - Derganc, Aleksandra (Slavistična revija, 2007)
The article discusses some recent contributions to the debate on the authenticity of the Old-Russian text Slovo o polku Igoreve. The emphasis is on the work of A. Zaliznjak - an advocate of authenticity of the text - who collected the previously published descriptions of its systematic linguistic features and added some findings of his own. Zaliznjak claims that linguistic systemic argumets have greater weight in the process of arguing for authenticity than the arguments of literary criticism and cultural history
Keywords: Literarne študije; Old Russian literature; Slovo o polku Igoreve; stara ruska književnost